2017
DOI: 10.1155/2017/2176749
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Selective Estrogen Receptor Modulator Raloxifene Are Mediated by Heme Oxygenase in Estrogen‐Deficient Rat

Abstract: Estrogens and raloxifene (RAL) have beneficial effects on certain cardiovascular indices in postmenopausal women characterized by estrogen deficiency. Heme oxygenase (HO) activity is increased by 17β-estradiol (E2) and RAL in estrogen-deficient rat resulting in vasorelaxation mediated by carbon monoxide. We determined the expressions of HO in cardiac and aortic tissues after ovariectomy (OVX) and subsequent RAL or E2 treatment. We investigated the effects of pharmacological inhibition of HO enzyme on the argin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
2
13
0
5
Order By: Relevance
“…Surgical castration induced a significant decrease in the cardiac HO enzyme activity and HO-1 concentration in both young and aged animals, while cyproterone acetate-treated rats possessed the lowest HO values as a result of the absolute block of androgen production. Similar to estrogen replacement therapy [23], we observed a protective role of testosterone administration against oxidative damages. Exogenous testosterone-induced amelioration was effective in both young and aged animals.…”
Section: Discussionsupporting
confidence: 63%
“…Surgical castration induced a significant decrease in the cardiac HO enzyme activity and HO-1 concentration in both young and aged animals, while cyproterone acetate-treated rats possessed the lowest HO values as a result of the absolute block of androgen production. Similar to estrogen replacement therapy [23], we observed a protective role of testosterone administration against oxidative damages. Exogenous testosterone-induced amelioration was effective in both young and aged animals.…”
Section: Discussionsupporting
confidence: 63%
“…Raloxifene restores acetylcholine-induced vasodilation and attenuates vasoconstriction induced by thromboxane receptor agonist in arteries of OVX hamsters fed a cholesterol-rich diet [ 101 ]. Raloxifene also increases heme oxygenase activity and inhibits myeloperoxidase in OVX animals, promoting vasodilation and preventing elevation of the ST segment, the isoelectric period between depolarization and repolarization on the electrocardiogram, further indicating a cardioprotective role associated with antioxidant and anti-inflammatory actions [ 102 ]. Hence, SERMs can be useful for preserving endothelial function and vascular hypersensitivity in coronary arteries in patients with hypercholesterolemia or hyperlipidemia involved in MI.…”
Section: Er Modulation and Mi: Preclinical Studiesmentioning
confidence: 99%
“…MPO-induced OxLDL peroxidation can result in reduced nitric oxide (NO) bioavailability, thereby weakening vasodilation and promotion of a pro-inflammatory state (43). Previous studies have shown that high MPO levels are associated with increased risks of cardiovascular events (44). Additionally, elevation in MPO levels as a result of leukocyte activation was negatively correlated with the tissue availability and microvascular permeability index of constitutive nitric oxide synthase (cNOS) (45).…”
Section: Discussionmentioning
confidence: 99%